The Economic Dimension of Using the Integration of Highway Sound Screens with Solar Panels in the Process of Generating Green Energy - Hasan Huseyin Coban; Wojciech Lewicki; Radosław Miśkiewicz; Wojciech Drożdż (Energies, 2022)
One of the research areas related to renewable energy sources is the search for new applications for currently used technologies. An important postulate is to achieve the synergy effect by including the existing infrastructure in this process. The innovation described in this article is the integration of solar cells into a modular sound barrier on the highway. The contribution of this article is mainly based on the introduction of the potential feasibility of the first Turkish solar highway, describing the installation of PV systems based on a multi-criteria evaluation (azimuth angle, loss of shade, and dirt). The aim of the study is to determine the economic dimension by examining the costs of implementing such an investment and answering the question concerning the efficiency of solar cells on sound barriers. The research took into account various scenarios regarding the shadow effect and inclination of solar panels and their impact on solar energy production in the example of a given case study, an identified urban area. The research is limited to the model for assessing the feasibility of solar cells on sound barriers based on NPV and the essence of the relationship regarding the LCOE averaged electricity costs. In this study, the function and technical parameters of solar cells are not specified, but the article is limited to the basic information and characteristics required to investigate the payback period and profitability of an investment. Research has shown that if the investment is carried out in accordance with the proposed model, the expected amount of energy produced is 62,257 kWh per year. This value corresponds to the average consumption of electricity in a household by 24 apartments for a given destination, or to providing energy for a selected electric vehicle for one year of its operation, at the same time leading to a significant reduction of CO2. The presented research can find practical application in the area of developing a strategy for the development and popularization of renewable energy sources while increasing the use of the existing road infrastructure, presenting an important postulate in promoting this type of solution for other geographic destinations.